Optimization of ultrasound-assisted extraction of naturally occurring glucosinolates from by-products of Camelina sativa L. and their effect on human colorectal cancer cell line - Pagliari, Stefania; Giustra, Chiara Maria; Magoni, Chiara; Celano, Rita; Fusi, Paola; Forcella, Matilde; Sacco, Grazia; Panzeri, Davide; Campone, Luca; Labra, Massimo (Frontiers in Nutrition, 2022)
The food waste generated by small and medium agro-industrial enterprises requires appropriate management and valorization in order to decrease environmental problems and recover high-value products, respectively. In this study, the Camelina sativa seed by-product was used as a source of glucosinolates. To begin, the chemical profile of the extract obtained using an international organization for standardization (ISO) procedure was determined by UPLC-HRMS/MS analysis. In addition, an extraction method based on ultrasound-assisted extraction was developed as an alternative and green method to recover glucosinolates. Main parameters that affect extraction efficiency were optimized using a response surface design. Under optimized conditions, the extract showed an improvement in extraction yield with a reduction in organic solvent amount compared to those obtained using the ISO procedure. Finally, the extract obtained with the ultrasound-assisted method was purified, tested on human colorectal cancer cell lines, and showed promising results.